2020
DOI: 10.1364/ao.389545
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond pressure transient detection of laser-induced thermal lens

Abstract: We use the thermal lens technique in the nanosecond time scale to describe the acoustic wave effect in liquids and the corresponding correlation with the speed of sound in the fluid, volumetric thermal expansion, and piezo-optic coefficient. These physical properties are found to be directly correlated to the anomalous effects observed in the transients at the nanosecond time scale, where acoustic waves dominate the thermal lens signal inducing an oscillating transient. Our results suggest the application of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…1 and described in detail in ref. 54 . A pulsed TEM 00 laser operating at 532 nm (Q-switched diode-pumped laser, Innolas, Model Dry-S, custom made) with a FWHM pulse width of 9 ns was used to excite the sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and described in detail in ref. 54 . A pulsed TEM 00 laser operating at 532 nm (Q-switched diode-pumped laser, Innolas, Model Dry-S, custom made) with a FWHM pulse width of 9 ns was used to excite the sample.…”
Section: Methodsmentioning
confidence: 99%
“…These contributions add up to produce the phase shift to the probe beam as where λ p is the probe beam wavelength. Considering only the centre of the probe beam spot at the detector plane in the far-field region, and using Fresnel diffraction theory, the relative far-field intensity signal S ( t ) results in 54 where V is an experimental parameter and w p the radius of the probe beam in the sample. The experimental parameters are listed in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…(5) . Considering only the center of the probe beam spot at the detector plane in the far-field region and using Fresnel diffraction theory, the far-field intensity signal can be written as [29] where is an experimental parameter and is the radius of the probe beam in the sample. The numerical calculation of in Eq.…”
Section: Pressure and Temperature Changes Due To Radiation Forcesmentioning
confidence: 99%
“…Alternatively, assuming semiinfinite space, with null heat flux in the interface z = 0, the solution of (eq 1) is as follows: 15 (11) with (12) This solution is a good approximation for the temperature profile, leading only to a small difference in the second face of the cuvette. In the low absorption limit, (eq 11) reduces to 15,16 The normalized intensity at the center of the probe beam at the detector plane is given as follows: 17 (14) where , in which ω 1p is the probe laser beam r a d i u s a t t h e s a m p l e a n d . In Figure 1, it can be observed that z 1 and z 2 are the distance from the probe beam waist to the sample and from the sample to the photodetector plane, respectively.…”
Section: T H Imentioning
confidence: 99%
“…The time dependence of the source is well approximated by the Dirac delta function for transients at a timescale bigger than the acoustic timescale. For transients at nanosecond order, acoustic waves may give rise to pressure effects, and a local pressure gradient is created, also contributing to the TL signal . This pressure gradient launches acoustic waves propagating away from the heated region before the thermal diffusion starts, being possible to neglect this acoustic effect for transients on millisecond scale.…”
Section: Theorymentioning
confidence: 99%